2021
DOI: 10.1177/2050313x211040680
|View full text |Cite
|
Sign up to set email alerts
|

A ‘never miss’ diagnosis: Ptosis secondary to metastatic breast cancer diagnosed as involutional ptosis and a review of the literature

Abstract: We present a case of ptosis secondary to metastatic lobular carcinoma of the breast which was initially diagnosed as involutional ptosis. A 67-year-old woman previously diagnosed with lobular carcinoma of the breast presented to our clinic with mild restriction of lateral gaze and persistent droopiness of her right eyelid (associated with decreased levator function) despite recent repair of a suspected involutional ptosis. Orbital magnetic resonance imaging revealed a mass in the right orbit which was biopsied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…A review of 116 eyes with orbital metastasis from breast cancer suggested that two thirds of the patients were at an age of more than 50 years at presentation and only 20 % had blepharoptosis. Invasive ductal carcinoma was noted in 27.8 % of metastatic lesions and was second to invasive lobular carcinoma [ 9 ]. This is a unique case of unilateral blepharoptosis of the mechanical type due to metastatic orbital disease originating from a primary ductal breast carcinoma causing restriction of the levator muscle due to the fibrotic nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 116 eyes with orbital metastasis from breast cancer suggested that two thirds of the patients were at an age of more than 50 years at presentation and only 20 % had blepharoptosis. Invasive ductal carcinoma was noted in 27.8 % of metastatic lesions and was second to invasive lobular carcinoma [ 9 ]. This is a unique case of unilateral blepharoptosis of the mechanical type due to metastatic orbital disease originating from a primary ductal breast carcinoma causing restriction of the levator muscle due to the fibrotic nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%